Fish Supply Chain Management Strategy Analysis for Warung Tegal (WarTeg) while Covid-19 Policy is Enforced in the Administrative City of South Jakarta - Telaumbanua, Kania Raflesia; Suhana, Suhana; Mulyani, Rita Yuni (Logistic and Operation Management Research (LOMR), 2023)
Warung Tegal is a small, lower-middle class restaurant in Indonesia. The name Warung Tegal, comes from Bahasa Indonesia, where "Warung" translates to "food stall" and Tegal refers to a city in Central Java. Warung Tegal, like many other small businesses, has been affected by the impact of the Covid-19 policies. In order to recover, Warung Tegal need to focused on improving supply chain management strategies especially for fish as one of the menus. This study aims to analyze supply chain management strategies in order to understand FSCM at Warung Tegal in the Administrative City of South Jakarta. The research method used was qualitative descriptive. The data was collected from ten respondents through structured interviews and observation. The sample for this study was the Warung Tegal managers in the Administrative City of South Jakarta. The results of the study showed that the fish at Warung Tegal is usually sourced from the nearest market, but the menu does not take into account the requests of the consumers and is never marketed through digital marketing due to the lack of knowledge in this field. The manager of Warung Tegal also stated that the restaurant's income has been reduced as a result of the Covid-19 policies. The study is limited by the time available for research and only covers the Administrative City of South Jakarta and not the entire DKI Jakarta area. Earlier study only identifies the influence of supply chain management strategies on the buying interest, with a positive result. While this study analyzes supply chain management strategies both before and after the enforcement of the Covid-19 policies.